The clergy and the nobility during the 1540s and 1550s of the sixteenth century - Godlewski, Łukasz (Saeculum Christianum. Pismo Historyczne, 2021)
The Executionist movement’s programme from the beginning of its existence revoked the privileges of the clergy not only in the legal but also in the economic field. The Chamber of Deputies wanted: the clerical estate holders to perform military service, the abolition of tithes, the taxation of the church, to devote “annats” to the defence of the country and jurisdictional demarcation between secular and ecclesiastical courts . The Chamber of Deputies, fighting against the clergy favoured by the king, unified their demands in order to act boldly in defence of their rights and gain new privileges. The final demands of the Executionist movement were formulated during the development of the Reformation and the transitional period caused by the change of the monarchs in the Republic of Nobles. The cumulation of these mechanisms in the middle of the 16th century not only stimulated the development and power of the Executionist movement but also intensified the conflict of interest between the clergy and nobility. The progress of the Reformation was accompanied by a growing dissatisfaction with the jurisdiction of the ecclesiastical courts over the nobility. The Chamber of Deputies formulated their suppositions depending on the situation outside and inside the country. The bishops failed to enforce the enforcement of judgments of the ecclesiastical courts. However, the right of sole judicial powers to pass verdicts connected with faith and religion were not taken away from the clergymen. It was just the opposite. Zygmunt August approved this privilege of the priests and at the same time executing verdicts on peerage was suspended. This case was, however, not completed and that is why succeeding parliaments worked on it further. The representatives of gentry did not manage to tax the income of church, despite serious efforts to do so. The king tried persistently to unite both political camps. However, the overextending of the whole Executionist programme by the representatives prevented the achieving of a compromise or any similar outcome.